Control system of spontaneous combustion in coal gangue dumps – a case study at Yuquan coal mine in China - Gang Wang; Qiqi Liu; Guoqiang Yan; Lulu Sun; Hongyuan Qu; Qingfang Han (Tehnički Vjesnik, 2017)
Spontaneous combustion in coal gangue dumps leads to pollution in the environment and damages ecosystem and human health. Mine operators usually fail to take effective measures against spontaneous combustion because of the inaccurate detection of the location of spontaneous combustion bursts. To address this issue, a control system of spontaneous combustion in coal gangue dumps was designed and constructed in this study. The control system is composed of a detection system of spontaneous combustion areas, a mobile prevention and extinguishing system of spontaneous combustion using liquid carbon dioxide (LCD), and an effect-checking system of spontaneous combustion in coal gangue dump. First, the detection system was used to detect the spontaneous combustion areas in the coal gangue dumps. LCD was then injected into the combustion areas with its pressure injection equipment to lower the temperature in the coal gangue dumps below the ignition point of coal gangue and to force oxygen out of the dumps. Finally, the effect-testing system was used to test the effects of the two systems. The spontaneous combustion in coal gangue dumps was controlled through a case study at Yuquan coal mine. Results show that the concentrations of index gases CO and H2S in the coal gangue dumps of Yuquan coal mine are below 24 and 6,6 ppm, and the internal temperature is below 70 °C, The cost per square meter of the control system of spontaneous combustion is approximately $8. Therefore, the proposed control system can economically and effectively control spontaneous combustion in coal gangue dumps, thereby preventing pollution in the environment.